Glassy-Winged Sharpshooter (suggested common name), Homalodisca coagulata (Say) (Insecta: Hemiptera: Cicadellidae: Cicadellinae) - Tracy Conklin; Russell F. Mizell, III (EDIS)
The glassy-winged sharpshooter, Homalodisca coagulata (Say), is a large leafhopper species native to the southeastern United States. It is one of the main vectors of the bacterium Xylella fastidiosa, a plant pathogen that causes a variety of plant diseases, including phony peach disease of peach and Pierce's disease of grape. Though usually not a serious pest in the area of its native distribution, the glassy-winged sharpshooter has recently been introduced into southern California, where it has become a serious threat to viticulture due to its ability to vector Pierce's disease.  This document is EENY-274, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2002. Revised: July 2004.